Paysages et problèmes du haut-bassin de l'Argens au cœur de la Provence Verte (Var occidental) - Jean Nicod (Physio-Géo)
The Argens upper watershed, upstream to the Valley Sourn gorges, is rich in remarkable travertine deposits: active waterfalls on Argens and old sites of Varages and Barjols. The work makes the synthesis of geomorphological observations realized by the author during its long practice (several decades) of this area. We find in it a lot of already published information, but also complements, cartographics in particular. If the inherited forms hold an important place, the current conditions of the travertine genesis are not neglected, due to the hydrological measures of the DREAL and to an hydrochemical study led in the years 1985-90. The development of travertines constructions seems forced by the conditions of the actual environment: reduction of the flows of low water levels under the influence of anthropogenic takings, water pollution and solid transport linked to the agricultural soil erosion during floods.